DIGITAL MEDIA, GLOBAL CULTURE, AND GENERATION Z ONLINE SHOPPING BEHAVIOR IN DENPASAR: THE MEDIATING ROLE OF MEDIA USAGE MOTIVATION - I Nyoman Sedana (PT Altin Riset Publishing, 2026)
This study aims to analyze the influence of digital media exposure and global cultural representation on media usage motivation and online shopping behavior among Generation Z in Denpasar City, while also assessing the mediating role of media usage motivation. A quantitative approach was employed using a cross-sectional survey design with 170 Generation Z respondents (aged 18–29 years) who are active users of social media and e-commerce platforms. Data analysis was conducted using Structural Equation Modeling (SEM) and the Sobel test. The findings reveal that digital media exposure significantly influences media usage motivation (β = 0.322; CR = 2.728; p = 0.006) and online shopping behavior (β = 0.211; CR = 2.501; p = 0.007). Global cultural representation demonstrates a stronger impact on both media usage motivation (β = 0.664; CR = 5.602; p < 0.001) and online shopping behavior (β = 0.603; CR = 5.581; p < 0.001). Furthermore, media usage motivation positively affects online shopping behavior (β = 0.368; CR = 3.899; p < 0.001). The Sobel test results indicate t = 2.273 (digital media) and t = 3.089 (global culture), both exceeding 1.96, thereby confirming that media usage motivation serves as a significant mediator. This study reaffirms the relevance of the Uses and Gratifications (U&G) theory in explaining the digital consumption patterns of Generation Z. The novelty lies in integrating the global culture variable into the U&G framework to explain Generation Z’s online shopping behavior within a culturally rooted urban context (Denpasar), which remains underexplored in the international literature. These findings enrich the discourse on cross-cultural digital consumer behavior and offer practical contributions to digital marketing strategies, digital literacy policies, and the empowerment of MSMEs through e-commerce.